RELATIONSHIP BETWEEN BOARD DIVERSITY, CORPORATE SUSTAINABILITY PRACTICES AND FINANCIAL PERFORMANCE OF FIRMS (Journal of Economics and Sustainability, 2020)
Research on board diversity (BD) has grown in the last two decades, but it is observed that the association between BD and financial performance (FP) of a firm is inconclusive to date. As the findings of the link between BD and FP are mixed, researchers suggest that the concerned parties might benefit from examining the critical effects of any third intervening variable on that relationship. Corporate sustainability practices (CSP) are an extensive management idea that assures long-term financial success and survival of a firm. However, the success of CSP is likely to increase when the board of directors (BOD) consists of diversified people who represent multiple stakeholders’ interests. Therefore, BD is likely to influence CSP, which, in turn, affects the FP of the firms. Accordingly, this paper proposes CSP as a mediator in the relationship between BD and FP of firms based on Stakeholder Theory. The key purposes of this article are to review the previous literature on BD, CSP, and FP, propose a research framework, and offers suggestions for future empirical research.